2016
DOI: 10.1016/j.jmb.2015.09.031
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis of Actin Organization by Vinculin and Metavinculin

Abstract: Vinculin is an essential adhesion protein that links membrane-bound integrin and cadherin receptors through their intracellular binding partners to filamentous actin, facilitating mechanotransduction. Here we present an 8.5 Å resolution cryo-EM reconstruction and pseudo-atomic model of the vinculin tail (Vt) domain bound to F-actin. Upon actin engagement, the N-terminal “strap” and helix 1 are displaced from the Vt helical bundle to mediate actin bundling. We find that an analogous conformational change also o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(116 citation statements)
references
References 72 publications
12
104
0
Order By: Relevance
“…The IA and VA mutations reduced the coprecipitation of vinculin to 42% and 53%, respectively, as previously reported [18, 22]. Given that the vinculin tail domain has two actin-binding surfaces [1820], these results suggest that the IA and VA mutations perturb one of the actin-binding surfaces, but the other binding surface may still bind actin. Although IA or VA mutation did not affect the binding of VBS3(talin)-activated vinculin to actin in vitro , these mutation are known to have effects on vinculin behaviors in cells [18, 22], indicating that vinculin is “fully” activated by a combination of talin with other binding partners in cells.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The IA and VA mutations reduced the coprecipitation of vinculin to 42% and 53%, respectively, as previously reported [18, 22]. Given that the vinculin tail domain has two actin-binding surfaces [1820], these results suggest that the IA and VA mutations perturb one of the actin-binding surfaces, but the other binding surface may still bind actin. Although IA or VA mutation did not affect the binding of VBS3(talin)-activated vinculin to actin in vitro , these mutation are known to have effects on vinculin behaviors in cells [18, 22], indicating that vinculin is “fully” activated by a combination of talin with other binding partners in cells.…”
Section: Resultssupporting
confidence: 84%
“…Interestingly, these mutations did not clearly reduce actin binding under mild activation conditions using VBS3(talin). Although the structure of Vt-actin is controversial [1820], in all models, Vt binds to two actin protomers in F-actin through two surfaces. Interestingly, double substitutions at both surfaces that were based on one structural model showed a drastic reduction in actin binding [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cDNAs encoding mouse FMN2 FH2 domain, corresponding to amino acids 1137–1529 (with or without a point mutation that resulted in a I1225 to A amino acid substitution) were expressed in BL21(DE3)-Rosetta2 E. coli cells (Millipore, DarmStadt, FGR) as His6-fusion proteins, following procedures used previously (Kim et al 2015). Briefly, expression was induced in log phase cultures with 0.5 mM IPTG at 16°C.…”
Section: Methods Detailsmentioning
confidence: 99%
“…From data derived from a variety of in vivo and in vitro techniques, it was concluded that MVt "tunes" actin filament bundles by altering the architecture and flexibility (73). Using high resolution cryo-electron microscopy, a sub-nanometer three-dimensional reconstruction of the vinculin tailactin complex was obtained (74). This study suggests that upon binding to actin, the N-terminal helix H1 of Vt unfurls, leading to vinculin dimerization and actin bundling.…”
Section: Metavinculinmentioning
confidence: 99%